Goodbye, Great White Father-Figure - Rogers, George W. (Anthropologica, 2022)
The development of government-native relations in Alaska is outlined from the Territorial period through to the granting of statehood, and in subsequent years. The wide variety of native peoples in Alaska has resulted in the growth of a number of native associations. These organizations have been riven with internal strife, and have seldom co-operated with each other. However, the oil discoveries on the North Slope of Alaska, and the proposed settlement of native claims to land in the states has provided a focus for concerted action for native rights organizations. The author suggests that a new type of native leader is emerging - one who can understand and interpret the internal social and economic dynamics of the state, and also deal justly with the large private and government entities involved in the present and future development of Alaska.